2020
DOI: 10.1177/0010414020919962
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Political Connections in Commercial Lawsuits: Evidence From Chinese Courts

Abstract: Like courts in democratic regimes, courts under authoritarianism play an important role in the regulation of complex economies. In particular, scholars suggest that authoritarian judiciaries are commonly encouraged to provide independent adjudication in the context of economic disputes between firms. Yet because regime insiders are often connected to firms, judges have strong incentives to consider the political implications of their decisions even in areas of the law where they are allegedly more independent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…This study challenges the conventional wisdom on the beneficial role of political connections in countries with weak institutions. A growing body of literature shows that political connections provide a helping hand to firms, mitigating regulatory difficulties, allowing better access to bureaucrats and better judicial resolutions, and producing considerable economic returns (Ang and Jia 2014; Gehlbach, Sonin, and Zhuravskaya 2010; Kung and Ma 2018; Szakonyi 2018; Truex 2014; Xu 2020). This study shows that the monetization of these benefits hinges on the status of the firm's revolving-door connections.…”
Section: Discussionmentioning
confidence: 99%
“…This study challenges the conventional wisdom on the beneficial role of political connections in countries with weak institutions. A growing body of literature shows that political connections provide a helping hand to firms, mitigating regulatory difficulties, allowing better access to bureaucrats and better judicial resolutions, and producing considerable economic returns (Ang and Jia 2014; Gehlbach, Sonin, and Zhuravskaya 2010; Kung and Ma 2018; Szakonyi 2018; Truex 2014; Xu 2020). This study shows that the monetization of these benefits hinges on the status of the firm's revolving-door connections.…”
Section: Discussionmentioning
confidence: 99%
“…Many states allow the possibility that arbitral decisions can be overridden and sent to domestic courts if they are thought to contravene domestic law. This creates opportunities for interference by states when decisions go against their interest, and opens up possibilities of the same types of interference based on corruption and connection identified by Xu (2020) in the Chinese court system. In our review of the UNCTAD's database on ISDS proceedings, we found 16 cases of ISDS cases where the underlying dispute stemmed from host state interference in commercial dispute resolution between firms; four of these cases involved disputes with SOEs.…”
Section: Theorymentioning
confidence: 97%
“…In many developing countries, however, assuring investors of independent contract enforcement through the legal system has proved difficult (Yu & Walsh, 2010), because judicial institutions are not seen as sufficiently independent (Dugan, Wallace, Rubins, & Sabahi, 2011; Ríos‐Figueroa & Staton, 2014). This is especially true of non‐democratic regimes where judges are appointed by the ruling regime and are often closely connected to national leaders as members of the regime party or through personal relationships (F. Chen & Xu, 2019; Xu, 2020).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when examining the panel effects in civil cases, we further control for special litigants. For example, state-owned enterprises, universities, and other public institutions are generally believed to be more advantageous in lawsuits (Wang, 2018;Xu, 2020); whereas farmers are often deemed "biggest losers" (He & Su, 2013). Therefore, we introduce two dummy variables in our model (see Appendix 11).…”
Section: Robustness Checksmentioning
confidence: 99%